Surgical stress-induced immune cell redistribution profiles predict short-term and long-term postsurgical recovery. A prospective study. - Rosenberger, Patricia H; Ickovics, Jeannette R; Epel, Elissa; Nadler, Eric; Jokl, Peter; Fulkerson, John P; Tillie, Jean M; Dhabhar, Firdaus S (The Journal of bone and joint surgery. American volume, 2009)
The experience of undergoing surgery is known to induce a short-term, fight-or-flight physiological stress response. As an optimum immune response at the site of surgery would enhance tissue repair, we examined surgical stress-induced immune cell redistribution profiles as predictors, and potential mediators, of short and long-term postoperative recovery. We tested the a priori hypothesis that predefined adaptive immune cell redistribution profiles observed during surgery will predict enhanced postoperative recovery.
Keywords: Arthroscopy; Female; Humans; Knee; Leukocytes; Longitudinal Studies; Lymphocytes; Male; Menisci, Tibial; Monocytes; Neutrophils; Predictive Value of Tests; Prognosis; Prospective Studies; Recovery of Function; Stress, Physiological